Pengaruh gaya kepemimpinan demokratis kepala sekolah dan motivasi kerja terhadap kinerja guru di sekolah dasar gugus I kecamatan pagaran kabupaten tapanuli utara tahun 2025/2026 - Lerita Situmorang; Andar G. Pasaribu; Wolter P. Silalahi (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2026)
This study aims to determine 1) the influence of the Principal's Democratic Leadership Style on elementary school teacher performance in Pagaran District, North Tapanuli Regency; 2) the influence of Work Motivation on Elementary School Teacher Performance in Pagaran District, North Tapanuli; and 3) the simultaneous influence of the Principal's Democratic Leadership Style and Work Motivation on Elementary School Teacher Performance in Pagaran District, North Tapanuli. This study used a quantitative survey method. The population was 50 elementary school teachers in Pagaran District, North Tapanuli. The sample consisted of the entire population, 50 people. Data were collected with a closed questionnaire consisting of 20 statement items for variable Y (Teacher Performance), and 20 statement items for variable X1 (Democratic Leadership Style of the Principal) and 20 statement items to measure X2 (Work Motivation) so that the total was 60 statement items. Before being used on real respondents, the instrument was first tested on 30 teachers in Pagaran District. The results of the instrument trial showed that all questionnaire items were valid and reliable. Data analysis techniques were carried out using descriptive analysis, variable categorization and parametric statistical analysis with simple and multiple linear regression equation tests, determination coefficient tests, t-tests and F-tests. The results of the data analysis show that: 1) There is a partial influence of the Principal's Democratic Leadership Style on the Performance of Elementary School Teachers in Pagaran District, North Tapanuli Regency of 16.9% and a fairly strong correlation value of 0.411 with a regression equation of Y = 37.818 + 0.396X1 and t count = 3.119 > t table (n-2 = 48) = 2.021; 2) There is a partial influence of Work Motivation on Elementary School Teacher Performance in Pagaran District, North Tapanuli Regency of 36.2% and a strong correlation value of 0.602 with a regression equation of Y = 27.395 + 0.577X2 thitung = 5.217 > t tabel (n-2 = 48) = 2.021 and 3) There is a simultaneous influence of Democratic Leadership Style of School Principal and Work Motivation on Teacher Performance in elementary schools in Pagaran District, North Tapanuli Regency of 44.2% and a strong correlation value of 0.665 with a regression equation of Y = 15.707 + 0.280X1 + 0.515X2 and Fhitung = 18.590 > F tabel (n-2 = 48) = 3.23. Thus, it is concluded that the research hypothesis is accepted.